The effect of exogenous progesterone on the quality of in vitro produced bovine embryos - Ketchum, Jaclyn; Rock, Kendra; Grieger, David M. (My University, 2017)
Maternal genetics can be advanced with the implementation of in vitro fertilization (IVF) in the beef and dairy industries. The efficiency of IVF-derived pregnancies is impacted by oocyte and embryo quality. An experiment was conducted in 2 replicates over a 2-year period to determine the effect of exogenous progesterone on the quality of IVF-produced embryos. In Year-1, mature beef cows were randomly assigned to either GnRH+CIDR (n=5) or GnRH-Only (n=5). All cows received GnRH (100ug) at day -7 and follicle stimulating hormone (FSH) on days -5, -4, -3 and -2. Cows in the GnRH+CIDR treatment received exogenous progesterone (Eazi-Breed CIDR®) on day -7 through day -1 while cows in the GnRH-Only group received only GnRH on day -7. Ovum pickup (OPU) via ultrasonography was conducted on day -1. Oocytes were collected via ovum pickup (OPU) on day -1 and matured for 24-hours prior to IVF. Embryos were cultured for 7 days post-fertilization in Year-1 and 6 days in Year-2. Embryos were stained on day 8 in Year-1 and day 7 in Year-2. Embryo quality was determined by cell count. In Year-2 blood samples were obtained on day -6, -3, and -1 to measure progesterone levels. Data were analyzed using the GLIMMIX procedure of SAS v.9.4 (Cary, NC), with cow as the experimental unit. In Year-1 and Year-2, cows that did not produce embryos that were viable at time of staining were excluded. In Year-1 there was no significant difference (p=0.4229) in cell number per embryo between GnRH+CIDR (n=4) and GnRH-Only (n=4) treatments. GnRH+CIDR cows had an average of 61.1 +/- 10.8 cells per embryo, while GnRH-Only cows average of 74 +/- 10.8 cells per embryo. In Year-2, there was a tendency (p=0.0507) embryos from GnRH+CIDR cows (n=3) to have increase in cells. The GnRH+CIDR treatment resulted in an average of 61.1 +/- 4.4 cells per embryo while the GnRH-Only treatment averaged 39.3 +/- 5.3 cells per embryo. Progesterone levels for Treatment GnRH+CIDR (n=5) were 6.8, 6.5, 2.8 ng/ml on days -6, -3, and -1, respectively. For GnRH-Only, progesterone levels were 7.7, 9.4, 6.9 ng/ml for days -6, -3, and -1 respectively. This study did not find an effect of exogenous progesterone on embryo production, although the high variability and few animals was most likely a factor.
Keywords: Fall 2017